Neutron and gamma ray fluences measurement at radial Beam Port 1 of TRIGA MARK II PUSPATI research reactor - Ashraff Rosdi M.A.; Goh P.S.; Idris F.; Shalbi S.; Sarkawi M.S.; Mohd Ali N.S.; Jamsari N.L.; Ramli A.S.; Azman A. (Institute of Physics Publishing, 2023)
Diffraction; Diffractometers; Facilities; Neutron diffraction; Neutrons; Reactor shielding; Research reactors; Shielding; Beam ports; Facility designs; Fluences; Gamma dose rate; Neutron diffractometer; Research results; Shielding materials; TLD-700; Gamma rays